ANALISIS STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN JUMLAH MAHASISWA DI STAI DARUSSALAM LAMPUNG - Siti Kholijah; Fitri Utami (EKSYDA: Jurnal Studi Ekonomi Syariah, 2023)
The paradigm in viewing education has begun to shift, from which education was originally viewed and studied as a social aspect, now people see education as a corporate. Therefore, many universities are competing with each other to attract prospective new students. This study aims to analyze marketing strategies in increasing the number of students at STAI Darussalam Lampung. The method used in this research is Variance Based SEM or Partial Least Square (PLS) analysis. Researchers found that the reasons for students in making decisions to continue their education at STAI Darussalam Lampung that need to be considered are increasing promotional media from students, lecturers, employees and alumni and stakeholders; student activities that need to be disseminated to the wider community as one of the promotional media; promotion through online and offline media; and increasing the scholarship quota for poor scholarships, achievement scholarships, tahfidz scholarships, and so on.